2019
DOI: 10.2147/ndt.s151253
|View full text |Cite
|
Sign up to set email alerts
|

<p>Addenbrooke&#39;s cognitive examination III in the diagnosis of dementia: a critical review</p>

Abstract: Addenbrooke’s cognitive examination III is a screening test that is composed of tests of attention, orientation, memory, language, visual perceptual and visuospatial skills. It is useful in the detection of cognitive impairment, especially in the detection of Alzheimer’s disease and fronto-temporal dementia. The aim of this study is to do a critical review of the Addenbrooke’s cognitive examination III. The different language versions available and research about the different variables that have relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 59 publications
0
89
0
4
Order By: Relevance
“…Cognitive function of the enrolled patients was assessed using Addenbrooke's cognitive examination version III (ACE) by a trained neuropsychologist before and 3 months after stenting. 12 Apart from cognitive function, demographic and clinical data of the study patients were also analyzed. A follow-up evaluation after 3 months was done to compare the cognitive function, occurrence of stroke or transient ischemic attack (TIA), renal failure, or other vascular events like acute myocardial infarction (MI) or death (due to any cause).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive function of the enrolled patients was assessed using Addenbrooke's cognitive examination version III (ACE) by a trained neuropsychologist before and 3 months after stenting. 12 Apart from cognitive function, demographic and clinical data of the study patients were also analyzed. A follow-up evaluation after 3 months was done to compare the cognitive function, occurrence of stroke or transient ischemic attack (TIA), renal failure, or other vascular events like acute myocardial infarction (MI) or death (due to any cause).…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function of the enrolled patients was assessed using Addenbrooke’s cognitive examination version III (ACE) by a trained neuropsychologist before and 3 months after stenting [ 12 ]. Apart from cognitive function, demographic and clinical data of the study patients were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…For example, as Brown et al [43] observed, only few patients with low-grade gliomas screened with MMSE had cognitive deterioration which is very often impaired in BT patients after radiation therapy. ACE III, like other neuropsychological tests (such as MMSE and MoCA), provides the psychologist with a quick and global cognitive screen of the patient, specifying both measures of each domain and the overall cognitive profile [44]. In the present study, BT patients had significant cognitive dysfunctions of memory, attention, orientation, and visual spatial functions.…”
Section: Discussionmentioning
confidence: 64%
“…Different tests have been proposed to evaluate cognitive function including memory, orientation, attention, reasoning and judgment, language skills, and attention [17,18,19]. Examples of such tools include the Eight-item Informant Interview to Differentiate Aging and Dementia (AD8), Annual Wellness Visit (AWV), General Practitioner Assessment of Cognition (GPCOG) and Health Risk Assessment (HRA), Memory Impairment Screen (MIS) (i.e., it is for testing verbal memory capability), Short Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE), Montreal Cognitive Assessment (MoCA) (i.e., it consists of a 30points scales [20] to identify subjects with MCI) [21], Addenbrooke's Cognitive Assessment (ACE) [22,23], and the Alzheimer's Disease Assessment Scale-Cognitive Subscale ADAS-Cog [24,25] (i.e., it examines attention, orientation, memory, language, visual perception, and visuospatial skills), the test can detect cognitive impairment that is related to AD and fronto-temporal dementia. Other examples include the Cambridge Assessment of Memory and Cognition, the Mini-Mental State Examination (MMSE) (it can assess impairments related to five cognitive functions such as orientation, attention, memory, language and visual-spatial skills by just asking subjects 11 questions [17]) test (its sensitivity is around 0.79, while its specificity is around 0.95) [26], the Saint Louis University Mental Status (SLUMS) (i.e., it encompasses a 30-point screening questionnaire to examine not only executive function but also orientation, memory, and attention) [27] and Cognitive Disorders Examination (Codex) (an ML-based assessment tool that combines a decision tree with the MMSE test and the clock drawing test to diagnose dementia.…”
Section: Cognitive and Neuropsychological Assessmentsmentioning
confidence: 99%